The relationship between digital transformation and corporate strategic communications in Southern EU countries - Valentina Mutsunska Palevska; Mijalce Gjorgievski; Todor Stojchevski (UTMS Journal of Economics, 2022)
The intensive technical-technological development and the Covid-19 pandemic have accelerated the digital transformation of communication agencies and corporate communication sectors. Until the outbreak of the pandemic, the professional and academic debate focused on new media and channels provided by digital technologies, for example: social media, the Internet or websites ( Duhé , 2017). In the current phrase digital technologies are extended in the context of models of digital technologies that can modify communication processes with stakeholders (Artur V, Page Society, 2021, Vaner , 2021). Accordingly, digital transformation in times of risky business turbulence in business is a priority focus of research interest because digital transformation produces changes that affect the productivity and economic sustainability of corporations. This paper investigates the relationship between COMTECHNA (digital technologies) and economic entities in Southern European countries, i.e. the degree of investment in digital transformation and the competitiveness of digital communications professionals in Russia. Macedonia and the impact on economic sustainability. Relevant data from 2021 was used for the analysis of the current situation. On the basis of the identified indicators, it was shown that economic entities do not invest enough in digital transformation, which results in a low level of competitiveness of digital communications professionals, and thus decreased productivity and unstable economic sustainability.
Keywords: I24; J29; O32; M37; M39; 330; digital transformation; business entities; digital communications professionals; business